2017
DOI: 10.14740/gr914w
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lower Gastrointestinal Bleeding: Characteristics and Clinical Outcome of Patients Treated With an Intensive Protocol

Abstract: BackgroundIn recent years major advances have been made in the management of patients with acute lower gastrointestinal bleeding. The aim of this study was to investigate the characteristics and clinical outcome of patients with acute lower gastrointestinal bleeding (ALGIB) treated with an intensive protocol.MethodsWe analyzed the medical records of 528 patients with ALGIB. All patients after hemodynamic stabilization underwent colonoscopy during the first 24 h of hospitalization and capsule enteroscopy when n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
6
0
4
Order By: Relevance
“…A study from USA showed that divericular bleeding (37%) was the most common cause of severe LGIB followed by ischemic colitis (13.2%), delayed post polypectomy induced bleeding (11.1%), rectal ulcer (8.9%), internal hemorrhoids (6.4%) and colon angiomas (6.4%) (Camus et al, 2017). Another study from western country discovered that the most common causes of LGIB were diverticulosis and ischemic colitis (Diamantopoulou et al, 2017). Study from Middle East indicated that the most common colonoscopic findings of LGIB were hemorrhoids followed by diverticulosis, neoplasm, rectal ulcer, colitis and polyps respectively, and colon was normal in 14.6% patients (Alruzug et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A study from USA showed that divericular bleeding (37%) was the most common cause of severe LGIB followed by ischemic colitis (13.2%), delayed post polypectomy induced bleeding (11.1%), rectal ulcer (8.9%), internal hemorrhoids (6.4%) and colon angiomas (6.4%) (Camus et al, 2017). Another study from western country discovered that the most common causes of LGIB were diverticulosis and ischemic colitis (Diamantopoulou et al, 2017). Study from Middle East indicated that the most common colonoscopic findings of LGIB were hemorrhoids followed by diverticulosis, neoplasm, rectal ulcer, colitis and polyps respectively, and colon was normal in 14.6% patients (Alruzug et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The higher incidence of haemorrhoidal bleeding may account for the shorter median length of stay of 3 days which in turn may result from selection bias in our local context with easier access to tertiary healthcare, as compared to other jurisdictions. Small bowel bleeding remains relatively uncommon (0.3%) but may be as high as 2–9% of LGIB in the literature, with angiodysplastic lesions being most prominent [ 29 , 30 ]. It is an important differential to consider in LGIB patients with normal endoscopic findings necessitating further investigation with video capsule endoscopy or double balloon enteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel bleeding remains relatively uncommon (0.3%) but may be as high as 2-9% of LGIB in the literature, with angiodysplastic lesions being most prominent. (29,30) It is an important differential to consider in LGIB patients with normal endoscopic ndings necessitating further investigation with video capsule endoscopy or double balloon enteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Lower Gastrointestinal Bleeding (LGIB), de ned as bleeding distal to the ligament of Treitz, remains a common presenting symptom for emergency general surgical patients. The annual incidence (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) cases per 100,000 adults) rises 200-fold between the 3rd and 9th decade of life. (1, 2) Amongst the elderly, the morbidity secondary to LGIB is exacerbated due to the interplay of multiple comorbidities, use of antiplatelet and/or anticoagulants and poor functional reserves.…”
Section: Introductionmentioning
confidence: 99%